Bauchi state of Nigeria 1995 Budget proposals - Bauchi state of Nigeria (Bauchi State : Directorate of Information, Military Governors Office, 1995)
This booklets contains statistical analysis of both capital and recurrent expenditure for Bauchi state government under the military administration in 1995.
asm; 05/03/19
Arch
Keywords: Budget; Bauchi State (Nigeria)